2014
DOI: 10.1080/17441692.2014.948480
|View full text |Cite
|
Sign up to set email alerts
|

Intimate relationships ofDevadasisex workers in South India: An exploration of risks of HIV/STI transmission

Abstract: Global literature on female sex workers suggests that being in an intimate relationship is associated with barriers to practising safe sex behaviours. Condom use within intimate relationships is often seen as a sign of infidelity and fosters mistrust which could affect longevity, trust and intimacy within partnerships. Using qualitative data from Devadasi sex workers and their intimate male partners in Bagalkot District, Karnataka, India, we examined both partners' perspectives to understand the quality and dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…High but inconsistent levels of condom use were reported among surveyed FSWs in both Asia and Africa. Most FSWs report using condoms with clients, but they are less likely to use protection with noncommercial or nonpaying partners, such as boyfriends, husbands, or regular lovers (Voeten ; Hoffman ; Ramanaik ; Deering ). A study in Swaziland noted that 69 percent of FSWs reported consistent condom use with new clients in the past month, but 32 percent had used condoms consistently with noncommercial partners and 23 percent had done so with all partners in this period (Yam ).…”
Section: Current Family Planning Practicesmentioning
confidence: 99%
“…High but inconsistent levels of condom use were reported among surveyed FSWs in both Asia and Africa. Most FSWs report using condoms with clients, but they are less likely to use protection with noncommercial or nonpaying partners, such as boyfriends, husbands, or regular lovers (Voeten ; Hoffman ; Ramanaik ; Deering ). A study in Swaziland noted that 69 percent of FSWs reported consistent condom use with new clients in the past month, but 32 percent had used condoms consistently with noncommercial partners and 23 percent had done so with all partners in this period (Yam ).…”
Section: Current Family Planning Practicesmentioning
confidence: 99%
“…Bagalkote and Vijayapura (earlier known as Bijapura) district have the worst health index ranking in the state [18], poor literacy levels and the highest rate of dropout among SC/ST girls in secondary school [19]. This region is also known for the Devadasi tradition, historically involving the dedication of young girls from the scheduled caste to a Goddess through a marriage ceremony, after which she served the temple and, in some cases, provided sexual services for priests and upper caste men [20,21]. Nowadays Devadasis engage in commercial sex, devoid of religious duties and social respect.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is supported by two recent studies. In a qualitative study with Devadasi in north Karnataka, IPs equated dominance and aggression with masculinity, and used violence to “discipline” their partner: for example, if the FSW disobeyed him, continued to see clients, or challenged traditional gender roles ( Ramanaik et al, 2014 ). In a separate study in north Karnataka, India, participants stated that the contravention of gender norms was viewed as a “mistake” on the part of the FSW that constituted one of the most important triggers of violence ( Blanchard, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, Ramanaik et al (2014) found that Devadasi women avoided condom negotiation and reporting of violence, which they perceived as potentially undermining their relationship with their IP. Blanchard found varying levels of acceptance of violence among FSWs: FSWs in this study consistently stated that violence was unacceptable—and yet continued to tolerate high levels of violence.…”
Section: Discussionmentioning
confidence: 99%